2013
DOI: 10.1364/ol.38.002026
|View full text |Cite
|
Sign up to set email alerts
|

Comb-calibrated frequency-modulated continuous-wave ladar for absolute distance measurements

Abstract: We demonstrate a comb-calibrated frequency-modulated continuous-wave laser detection and ranging (FMCW ladar) system for absolute distance measurements. The FMCW ladar uses a compact external cavity laser that is swept quasi-sinusoidally over 1 THz at a 1 kHz rate. The system simultaneously records the heterodyne FMCW ladar signal and the instantaneous laser frequency at sweep rates up to 3400 THz/s, as measured against a free-running frequency comb (femtosecond fiber laser). Demodulation of the ladar signal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(40 citation statements)
references
References 20 publications
1
33
0
3
Order By: Relevance
“…The advent of a new generation of mobile atomic clocks [16,17] and comb-based free-space optical frequency transfer [18] could permit precise timing networks, tests of relativity, and clock-based geodesy [19,20]. Finally, the precision and accuracy of comb-based LADARs are attractive for manufacturing and remote sensing in general [21][22][23][24][25][26][27][28][29][30]]. Here we demonstrate a self-referenced fiber frequency comb that can operate in the field while retaining its optical coherence and 5 femtosecond-level timing-jitter.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of a new generation of mobile atomic clocks [16,17] and comb-based free-space optical frequency transfer [18] could permit precise timing networks, tests of relativity, and clock-based geodesy [19,20]. Finally, the precision and accuracy of comb-based LADARs are attractive for manufacturing and remote sensing in general [21][22][23][24][25][26][27][28][29][30]]. Here we demonstrate a self-referenced fiber frequency comb that can operate in the field while retaining its optical coherence and 5 femtosecond-level timing-jitter.…”
Section: Introductionmentioning
confidence: 99%
“…As the detected beat frequency is proportional to the desired range measurement through the speed of light and the chirp rate, the latter is the main parameter that must be calibrated to construct an accurate FMCW ladar system. Although characterization against an optical frequency comb showed that the sweep can be linearized and calibrated to less than 15 ppb [3,9,10], ∼ppm accuracy would be sufficient for most applications and a less-expensive traceable calibration method would be highly desired. Therefore, we focus in this paper on calibration by use of molecular frequency references HCN (C-band) or CO (L-band).…”
Section: Introductionmentioning
confidence: 99%
“…The sub-millimeter range resolution provided by the large bandwidth and the high sensitivity provided by coherent detection allows these FMCW ladar systems to make micron level precision range measurements at standoffs exceeding 10 m and to multiple simultaneous returns [3]. Calibration of these sources against molecular references [4] or optical frequency combs [5], [6] can provide ppm level or ppb level accuracy, respectively. Additionally, the multi-return capability of FMCW ladar allows measurement of multiple surfaces of (or through) transparent materials or obscurants.…”
Section: Introductionmentioning
confidence: 99%